Proteomic fertility markers in ram sperm - Hitit, Mustafa; Ozbek, Mehmet; Ayaz-Guner, Serife; Guner, Huseyin; Oztug, Merve; Bodu, Mustafa; Kirbas, Mesut; Bulbul, Bulent; Bucak, Mustafa Numan; Ataman, Mehmet Bozkurt; Memili, Erdogan; Kaya, Abdullah (Elsevier BV, 2021)
Precise estimation of ram fertility is important for sheep farming to sustain reproduction efficiency and profitability of production. There, however, is no conventional method to accurately predict ram fertility. The objective of this study, therefore, was to ascertain proteomic profiles of ram sperm having contrasting fertility phenotypes. Mature rams (n = 66) having greater pregnancy rates than average (89.4 ± 7.2%) were assigned into relatively-greater fertility (GF; n = 31; 94.5 ± 2.8%) whereas those with less-than-average pregnancy rates were assigned into a lesser-fertility (LF; n = 25; 83.1 ± 5.73%; P = 0.028) group. Sperm samples from the outlier greatest- and least-fertility rams (n = 6, pregnancy rate; 98.4 ± 1.8% and 76.1 ± 3.9%) were used for proteomics assessments utilizing Label-free LC-MS/MS. A total of 997 proteins were identified, and among these, 840 were shared by both groups, and 57 and 93 were unique to GF and LF, respectively. Furthermore, 190 differentially abundant proteins were identified; the abundance of 124 was larger in GF while 66 was larger in LF rams. The GF ram sperm had 79 GO/pathway terms in ten major biological networks while there were 47 GO/pathway terms in six biological networks in sperm of LF rams. Accordingly, differential abundances of sperm proteins between sperm of GF and LF rams were indicative of functional implications of sperm proteome on male fertility. The results of this study emphasize there are potential protein markers for evaluation of semen quality and estimation of ram sperm fertilizing capacity.
Keywords: Male; Proteomics; Proteome; Spermatozoa; Fertility; Tandem Mass Spectrometry; Animals; Biomarkers; Sheep, Domestic; Chromatography, Liquid; 2. Zero hunger